Territorial control and the scope and resilience of cannabis and other illegal drug crop cultivation - Pierre-Arnaud Chouvy (EchoGéo)
As revealed by the examples of Morocco, northeast India, Afghanistan, Burma/Myanmar, and the United States of America, degrees of politico-territorial control or law-enforcement deficit by the state can explain, to some extent, the existence of large expanses of illegal drug cultivation. Causes of politico-territorial control deficit are many and non-exclusive. They include armed conflicts, corruption, loosely integrated territories, and lack of financial, human and material means of asserting state control. Large-scale illegal drug crop cultivation can take place according to three main scenarios: that of a full-fledged but inefficient war on drugs; that of toleration, for various motives, of illegal drug plant cultivation by the state (which can amount to negotiated but effective control); and that of the militarily-challenged state that cannot exert full control over its territory. The fact that total politico-territorial control by the state, no matter how powerful and resourceful, is deemed impossible, shows that the war on drugs is doomed to fail despite how many battles were won. Eventually, the very limits of the state’s politico-territorial control, when applied to counter-narcotics and law enforcement, implicitly question the illegality of a practice that is considered legitimate by many.